INOVASI KURIKULUM LEMBAGA PENDIDIKAN TENAGA KEPENDIDIKAN PERGURUAN TINGGI AGAMA ISLAM - Nur Ali (el-hikmah, 2012)
The Minister of national education and The Minister of religious affair have decreed that the teacher must have a certain academic qualification and competencies, and teacher certification if he/she wants to become a professional teacher. Beside that, the academic competencies of teacher and its certification have to appropriate with the competencies standard of curriculum in the school. So, the institution of  educational manpower education  in the Islamic higher education (IHE) has to be able to realize the policies by conducting  the curriculum innovation  based on the policies of  education and the needs of stake holders and the religious  character of  IHE.   There are seven model of  innovation can be used  (i) incremental, (ii) radical, (iii) modular, (iv) architectural, (v) top-down model,  (vi) bottom-up model, and (vii)  model of N-3; niteni, niroake  and nambahake. The process of innovation include;  (i) recognizing a problem or need, (ii) research, (iii) development, (iv) commercialization, (v) deffusion and adoption, dan (vi) conceguences. The approaches of curriculum innovation are (i) produktive, (ii) humanistic, (iii) democration, (iv) clasic, (v) romantic, and (vi) modern. The strategies  in curriculum innovation are  the rational-Empirical Strategy, the normal-Reeducative Strategy, and the  Power-Coercive Strategy.